A Causal Relationship Model of Factors Influencing Performance Competency Work of Policy and Planning Analysts Educational Service Areas Office in Northeastern Region: A Causal Relationship Model of Factors Influencing, Performance, Policy and Planning Analysts - Sriphuttiban, Woranuch; Kajitnatitham, Maleerat; Vongprasert, Jamlong (Ubon Ratchathani Journal of Research and Evaluation, 2024)
The study aimed to: 1) Develop a model of causal relationship among factors that influence the performance of policy and planning analysts. Education service area office in the northeast. 2) Examine the consistency of factors influencing the performance of policy and planning analysts. Education service area office in the northeast with empirical data. And 3) Study of direct effect, Indirect effect and the total effect of factors effect the performance of policy and planning analysts. Education service area office in the northeast. The sample used in the research is policy and planning analysts working in the policy and planning group. Education Service Area Office in the Northeast The sample size of 270 people are randomly assigned. Multi-step method. The research instrument was a questionnaire with a 5-level evaluation scale, 1 copy, It has a reliability value of .982. Statistics used in data analysis include: 1) Basic statistics include frequency and percentage, mean and standard deviation, distribution coefficient and 2) Statistics used in hypothesis testing include the Relative Chi-square, the Comparative Fit index, The root mean square Error of Approximation. The Standardized Root Mean Square Residual. Structural Equation Analysis. The research findings were as follows: The results of developing model of the relationship of factors that influence the performance of policy and planning analysts in educational service area offices. In the northeast that the researcher developed. There are variables that are studied. Consists of 3 latent variables and 13 observable variables obtained correlation values between 78 pairs of variables. It was found that the correlation matrix of observed variables. There are correlation coefficients ranging from .380 to .863, whit statistical significance at the .01 level, a total of 78 pairs and every pair of variables are positively related. There were 19 variables with a very high level of correlation. by proactive operations and looking at the overall picture has the highest relationship and there were 49 variables with a high level of correlation, while there were 10 variables with a moderate level of correlation, And the variables with the lowest level of relationship are compensation and benefits and work experience. Relationship model of factors that influence the performance of policy and planning analysts in educational service area offices. in the northeast that the researcher developed There is a Relative Chi-square value equal to 1.9290 The Comparative Fit index value is equal to 0.974. The root mean square Error of Approximation equals to 0.049. The Standardized Root Mean Square Residual is equal to 0.043. In conclusion, the hypothesized model is consistent with the empirical data. Results of study of direct effect, indirect effect and total effect that the researcher developed. It has the highest coefficient of effect is the total effect of motivating factors on the performance of policy and planning analysts. The value is equal to 0.891 with statistical significance of .01. Second is the total effect from supporting factors, with a value of 0.659 with statistical significance of .01. and the lowest is the total effect from personal factors with a value of 0.363 with statistical significance of .01